Analisis Pengendalian Kualitas Tahu Menggunakan Metode Seven Tools (Studi Kasus di Tahu Takoa Riski) - Arief, Zidan Aghny; Qhifari, M Oza Raihan; Efendi, Irfan (MASALIQ, 2024)
Quality control is an essential approach that should be implemented from the pre-production stage throughout the production process until the final product is produced. This study aims to identify the prevailing form of deficiency, investigate the underlying causes of the defect, and propose suggestions for enhancement. Takoa Riski Tahu is a micro, small, and medium enterprise (MSME) located in North Tidar, South Magelang, Magelang City. This particular enterprise specializes in the production of white tofu. Takoa Riski Tofu can manufacture 16390 units of tofu in one month. This study uses the seven tools technique to ascertain the prevailing categories of flaws and the underlying factors responsible for their occurrence. According to studies, it is established that there are three distinct categories of defects: appearance, size, and filth. Appearance faults have the highest prevalence, accounting for 39.7% of all defects. Size problems are the second most common, making up 33.5% of defects, while filth defects are the least prevalent, comprising 26.7%. The factors contributing to defects include human error, machinery malfunction, subpar materials, inefficient processes, and unfavourable environmental conditions.